Becoming a principal in Indonesia: Possibility, pitfalls and potential - Sumintono, B.; Sheyoputri, E.Y.A.; Jiang, N.; Misbach, I.H.; Jumintono, J (National Institute of Education, Singapore, 2015)
The preparation and development of school leaders is now considered to be fundamental to school and system improvement. In the pursuit of educational change and reform, the leadership of the principal is deemed to be of critical importance. This qualitative study is part of a large scale research project that is exploring principal preparation and development in seven different countries. In particular, this article focuses on how public secondary school principals in Indonesia are prepared, developed and selected for their role. Disappointingly little is known from the empirical literature about being a principal in Indonesia or about principal preparation and development. Therefore this contemporary, descriptive, non-experimental qualitative study focused on a purposive sample of 18 public secondary school principals in four different provinces in Indonesia. The initial findings reveal that even though principal training has been standardized in Indonesia and is now a compulsory part of a principal certification process, micro-political influences still currently govern the appointment of school principals.